Pengaruh Kualitas Produk dan Harga Terhadap Keputusan Pembelian Produk Emina Kosmetik - Nugroho, Poso; Christina Dewi Wulandari; Tri Damayanti; Sahdina Nadila (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This study aims to analyze the influence of product quality and price on the purchase decision of Emina Cosmetic products, both partially and simultaneously. The research method used is quantitative. The population in this study consists of consumers who have purchased Emina Cosmetic products at least once and are female. The sample size is set at 100 respondents. The analysis method in this study uses primary quantitative data, with the following testing stages: validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, T-test, F-test, and coefficient of determination using SPSS 27 statistical software. The sampling method used in this study is non-probability sampling with a purposive sampling technique. The results of the study show that, partially, the Product Quality variable influences the Purchase Decision with a significance value of 0.001 < 0.05 or a t-value of 3.430 > t-table of 1.984. Price partially influences the Purchase Decision with a significance value of 0.001 < 0.05 or a t-value of 3.421 > t-table of 1.984. Simultaneously, Product Quality and Price influence the Purchase Decision with a significant value of 0.000 < 0.05.